2018
DOI: 10.1002/csr.1694
|View full text |Cite
|
Sign up to set email alerts
|

Promoting employee's proenvironmental behavior through green human resource management practices

Abstract: Success of organizational initiatives for environmental sustainability hinges upon employees' proenvironmental behaviors. One of the contemporary important challenges faced by HR professionals is to ensure proper integration of environmental sustainability into human resource policies. The green human resource management (green HRM) has emerged from organizations engaging in practices related to protection of environment and maintaining ecological balance. The aim of this study is to examine the effects of gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

50
775
3
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 632 publications
(838 citation statements)
references
References 77 publications
50
775
3
10
Order By: Relevance
“…The above arguments were endorsed by Dumont et al () in a study among Chinese employee where they discovered that GHRM had a both direct and indirect influence on in‐role green behaviors whereas it influenced extra‐role green behaviors only indirectly through the creation of psychological green climate. Further, in a very recent attempt, Saeed et al () demonstrated the positive effect of GHRM practices on employee pro‐environmental behaviors among employee from a wide variety of industries in Pakistan.…”
Section: Theoretical Framework and Research Propositionsmentioning
confidence: 99%
“…The above arguments were endorsed by Dumont et al () in a study among Chinese employee where they discovered that GHRM had a both direct and indirect influence on in‐role green behaviors whereas it influenced extra‐role green behaviors only indirectly through the creation of psychological green climate. Further, in a very recent attempt, Saeed et al () demonstrated the positive effect of GHRM practices on employee pro‐environmental behaviors among employee from a wide variety of industries in Pakistan.…”
Section: Theoretical Framework and Research Propositionsmentioning
confidence: 99%
“…Another reason behind the implementation of green HRM is to promote green organizational culture and enhance employee behaviors related to the environment. Academic research suggests that green HRM practices affect employee proenvironmental behavior (Saeed et al, ). Green HRM tools, procedures, and practices enhance employees' participation in the process of eco‐friendly behavior, such as to reduce environmental waste, to increase efficiency in the cost elimination process, and to improve the products (Robertson & Barling, ).…”
Section: Theoretical Underpinning and Hypothesesmentioning
confidence: 99%
“…Many of the research studies into green HRM have used green psychological climate (Dumont, Shen, & Deng, ), intrinsic motivation (Afsar, Badir, & Kiani, ), proenvironmental psychological capital (Saeed et al, ), employees' organization commitment (Kim et al, ), organizational citizenship behavior toward the environment (Paille, Chen, Boiral, & Jin, ), and environmental management system implementation (Wagner, ) as mediators in explaining employees' extra‐role green behavior, their proenvironmental behavior, and hotels' environmental performance respectively. However, few scholars draw attention to the possible influence of an individual's passion for environmental‐related outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to empirical analysis of the sustainable HRM perspective, numerous qualitative (Guerci & Carollo, ; Haddock‐Millar, Sanyal, & Müller‐Camen, ) and quantitative studies (Diaz‐Carrion, López‐Fernández, & Romero‐Fernandez, ; Guerci, Longoni, & Luzzini, ; Saeed et al, ; Tang, Chen, Jiang, Paillé, & Jia, ) have been undertaken. Nevertheless, the field is somewhat fragmented, and given the growing sustainability concerns in the HRM literature, the following bibliometric analysis seeks to offer a “state‐of‐the‐art” snapshot of the field to gain a better understanding of its evolution and identify future research paths.…”
Section: Theoretical Frameworkmentioning
confidence: 99%